Posing: The Sociological Routine of a Serial Killer - Forsyth, Craig J. (American journal of criminal justice, 2015)
This paper describes the serial killer Ronald Dominique. Ronald killed at least 23 men in southeast Louisiana between 1997 and 2006. The author of this paper served as a mitigation investigator/expert on his case and has worked in over 300 criminal cases since 1988, most of which were capital murder, but also include second degree murder, manslaughter, armed robbery, rape, and habitual offender hearings. In his capacity as a mitigation investigator he interviewed Ronald multiple times and his friends and family on several occasions. This author examines Ronald’s victims; the acts which killed them; Ronald’s life; and how others saw him. The literature on serial killers is discussed and applied to Ronald crimes and his life. Ronald was gay and his victims were either gay or hustlers who were willing to have sex with gay men for money. Using several theories, the author discusses explanations for serial murder. Implications for police investigators are discussed.